Developing A Clinical Evidence Retrieval Service in Response to the COVID-19 Pandemic - Chew, Wei Z.; Liew, Su M.; Engkasan, Julia P.; Hairi, Noran N.; Ng, Ka T.; CL, Teng; Shunmugam, Ranita H.; Yuen, Choo W.; Ng, Chirk J. (International Journal of Medical Students, 2023)
In response to the COVID-19 pandemic, policies, and treatment guidelines underwent rapid and frequent change. This threatened to disrupt the measured practice of evidence-based medicine (EBM), which relies on tried-and-tested interventions. The uncertainty was compounded by the overwhelming amount of misinformation disseminated via social media. Thus, arose a need for valid information to guide clinical practice. COVID-19 Evidence Retrieval Service (CERS), an evidence retrieval service piloted at a local and then rolled out at a national level, was conceived and developed to address this issue. This article describes the components and implementation of the (CERS), The service’s objective was to review the available medical literature for the best evidence to answer COVID-19-related questions posed by practicing clinicians. Team members providing the service comprised librarians, clinicians, public health specialists, and medical students. Multiple lessons were learned through the development and provision of CERS. Firstly, the rapid nature of the pandemic necessitated adaptations of the current practice of EBM. Secondly, all work processes were conducted online, which proved efficient and sustainable. Thirdly, Lower Middle-Income Country (LMIC) oriented services such as CERS were valid because they provided more relevant questions to resource-limited healthcare systems. Our experience has reinforced that an integrated, evidence-based retrieval service is feasible and valuable to support healthcare workers and policymakers in making informed decisions by performing a systematic appraisal. Crucially, medical students and young healthcare professionals can play a pivotal role in setting up these services.